KARAKTERISTIK KLINIKO HISTOPATOLOGI NODUL TIROID DARI 1 JANUARI 2016 – 31 DESEMBER 2017 DI LABORATORIUM PATOLOGI ANATOMI FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA/ RSUP SANGLAH DENPASAR - Silvia Nuhyil Indriani; I Gusti Ayu Sri Mahendra Dewi; Ni Putu Sriwidyani; Ni Putu Ekawati (E-Jurnal Medika Udayana, 2021)
ABSTRACT Backgrounds : Thyroid nodule abnormalities are quite common in the community. The incidence of thyroid nodules increases with age with a high incidence rate in women. Goals : This study aims to determine the clinico histopathology characteristic of thyroid nodules from 1 January 2016-31 December 2017 at Pathology Anatomy Laboratory Sanglah General Hospital Denpasar. Methods : This research is a cross-sectional retrospective study obtained from patient medical record data in the Pathology Anatomy Laboratory, Sanglah General Hospital. Data were analyzed using the SPSS version 22.0 program. Result : Obtained 330 samples with thyroid nodules. The distribution of women is more (84.5%) cases compared to men (15.5%), with the highest age range occurring at the age of 41-50 years and 51-60 years, respectively 89 (27.0%) cases. Most diagnoses were 206 (62.4%) cases of non neoplastic, with the most lateralization occurring in all thyroid lobes in 233 (70.6%) cases. Conclusion : Thyroid nodule abnormalities tend to be more common in women aged 41-60 years, are benign and occur in all thyroid lobes. Keywords: Thyroid Nodules, Clinico Histopathology